2020
DOI: 10.1136/bcr-2020-235117
|View full text |Cite
|
Sign up to set email alerts
|

Euglycaemic diabetic ketoacidosis in a 43-year-old woman with type 2 diabetes mellitus on SGLT-2 inhibitor (empagliflozin)

Abstract: We report a case of euglycaemic diabetic ketoacidosis (EDKA) in a 43-year-old woman with type 2 diabetes mellitus who presented to the emergency department with problems of vomiting, cough, shortness of breath and generalised weakness after following a ketogenic diet for 2 weeks. Therapy with sodium glucose transport protein-2 empagliflozin had been started 2 months prior. Initial evaluation revealed high anion gap metabolic acidosis with blood glucose level of 169 mg/dL. Treatment for EDKA with fluid resuscit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This situation leads to a glucagon release that causes an elevation of the glucagon to insulin ratio, increasing the gluconeogenesis, lipolysis and ketogenesis [3]. This mechanism can be exacerbated because of the dehydration caused by the natriuretic and osmotic effect on glucose and sodium cotransporter that SGLT2 has, which leads to a secondary osmotic effect on reabsorption of water [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation leads to a glucagon release that causes an elevation of the glucagon to insulin ratio, increasing the gluconeogenesis, lipolysis and ketogenesis [3]. This mechanism can be exacerbated because of the dehydration caused by the natriuretic and osmotic effect on glucose and sodium cotransporter that SGLT2 has, which leads to a secondary osmotic effect on reabsorption of water [8].…”
Section: Discussionmentioning
confidence: 99%
“…The process by which can produce EDKA is not other than the main mechanism of action of the drug: to enhance excretion and block reabsorption of glucose in the proximal convoluted tubule, leading to a loss of urinary glucose which develops a state of carbohydrate starvation and boosting a glucagon/insulin ratio disbalance. Additionally, it has been found that SGLT2 inhibitors can also stimulate the release of glucagon from the pancreas, worsening the dysregulation above mentioned by maintaining euglycemia [8].…”
Section: Discussionmentioning
confidence: 99%